2013
DOI: 10.1021/bm400879x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Labeling and Characterization of Cellulose Nanocrystals with Varying Charge Contents

Abstract: Cotton-source cellulose nanocrystals (CNCs) with a range of surface charge densities were fluorescently labeled with 5-(4, 6-dichlorotriazinyl) aminofluorescein (DTAF) in a facile, one-pot reaction under alkaline conditions. Three CNC samples were labeled: (I) anionic CNCs prepared by sulfuric acid hydrolysis with a sulfur content of 0.47 wt %, (II) a partially desulfated, sulfuric acid-hydrolyzed CNC sample, which was less anionic with an intermediate sulfur content of 0.21 wt %, and (III) uncharged CNCs prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 28 publications
(49 reference statements)
2
81
1
Order By: Relevance
“…This corresponds to a crystallinity drop of The amount of grafted fluorophores is very significant and consists of a large increase when compared with the work of Nielsen et al [20] which reported grafted amounts of [24] or 0.02-0.2 μmol/g 5-(4, 6-dichlorotriazinyl) aminofluorescein (DTAF) achieved by Abitbol et al [44] The absorption spectra of the Cz-a-CNC1, Cz-a-CNC2 and Cz-a-CNC3 ( proportional with the absorption peaks while with increasing concentration, e.g. at 0.08 mg/mL, all the emission spectra display almost the same intensity (Figure 8).…”
Section: Resultsmentioning
confidence: 83%
“…This corresponds to a crystallinity drop of The amount of grafted fluorophores is very significant and consists of a large increase when compared with the work of Nielsen et al [20] which reported grafted amounts of [24] or 0.02-0.2 μmol/g 5-(4, 6-dichlorotriazinyl) aminofluorescein (DTAF) achieved by Abitbol et al [44] The absorption spectra of the Cz-a-CNC1, Cz-a-CNC2 and Cz-a-CNC3 ( proportional with the absorption peaks while with increasing concentration, e.g. at 0.08 mg/mL, all the emission spectra display almost the same intensity (Figure 8).…”
Section: Resultsmentioning
confidence: 83%
“…Table shows the different sulfur contents (%S) and the zeta potential after the different treatments of CNCs. The sulfur content was measured using elemental analysis, and the value for the original CNC sample (CNC‐2) was in the same range as the CNC sulfur content reported by other research groups . From Table , it can be seen that the two samples that were desulfated had lower sulfur content and a higher zeta potential compared with the original CNCs.…”
Section: Methodsmentioning
confidence: 85%
“…Their visualisations by scanning electron microscopy (SEM) or atomic force microscopy (AFM) require time and effort for detailed observation due to small observation fields (AFM in particular) making these techniques prohibitive for detailed analysis (Iwamoto et al 2013). As an alternative, fluorescent labelling (using FITC (Dong and Roman 2007), isothiocyanate, succinimidyl ester, pyrene, dichlorotriazine (Abitbol et al 2013;Huang et al 2013), etc. allows extensive microscopy studies (from trivial, distribution patterns' observations up to distribution and cellular uptake follow-up (Generalova et al 2009).…”
Section: Introductionmentioning
confidence: 99%